PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DISELINGI ICE BREAKING TERHADAP HASIL BELAJAR MATEMATIKA VIII MTsN 6 TANAH DATAR - Ummah, Biiznillah Khaira (Departemen Matematika, 2024)
Looking at the results of the lesson is one way to tell whether the lecture was successful. Nonetheless, the eighth grade at MTsN 6 Tanah Datar maintains dismal performance in this domain. It is affected by the chosen learning paradigm. To make it even more successful, may include Ice Breaking into the Jigsaw Cooperative Learning Model. The purpose of this research was to determine if eighth graders at MTsN 6 Tanah Datar might improve their mathematical understanding by using a model that included icebreakers. This kind of quantitative research is a form of quasi-experimental study that uses a control group that only takes the exam after the fact. Students in grades VIII.1 and VIII.8 from MTsN 6 Tanah Datar were the subjects of the study. The method used was a descriptive learning outcome evaluation. The t-test that was used to analyze the data produced a p-value of 0.014. With a p-value less than 0.05, we may affirm that H0 is not true. Students learn more mathematics when teachers use the Jigsaw model in conjunction with icebreakers than when teachers use more traditional techniques.Keywords– Mathematics Learning Outcomes, Jigsaw, Ice Breaking, Conventional Learning Model